Sea lions (Otaria flavescens) from the end of the world: insights of a recovery - Milano, Viviana Natalia; Grandi, Maria Florencia; Schiavini, Adrian Carlos Miguel; Crespo, Enrique Alberto (Polar Biology)
To understand the recovery process and population dynamics of species that were severely depleted, it is essential to monitor their population size and habitat changes throughout their distribution. The South American sea lion (SASL, Otaria flavescens) provides an opportunity to investigate the process of a reduction from sealing and the subsequent recovery in a marine mammal species. Its abundance was depleted throughout its distribution, but the most affected extraction areas were Península Valdés (northern Patagonia) and Tierra del Fuego (Fuegian Archipelago). The aims of this work are to present recent estimates of the population abundance and then analyze changes in social composition, distribution, population size and trend of SASL at their sub-Antarctic distribution. We made an aerial survey of Fuegian Archipelago colonies and compared the results with historical compilation data registered since 1948. In total 49 colonies were surveyed (24 exclusive of SASL, 15 shared with South American fur seals and 10 sites were abandoned). An abundance of 7684 individuals (including 440 pups) was recorded. There was an increase of population abundance, with a change of the social composition and distribution of some colonies through time. The average annual percentage of population changes yields a growth of 8.8%. This value completes the population growth trend data throughout Southwestern Atlantic for SASL, and shows that there is an increasing latitudinal gradient of these rates. We discuss possible explanations related to differences in the beginning of the recovery, or in reactions to local environmental constraints, or migration from Pacific stocks. Fil: Milano, Viviana Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Grandi, Maria Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional ...